Hubungan Rasio Trigliserida-High Density Lipoprotein pada Luaran Stroke Iskemik di RSUP Prof. Dr. R. D. Kandou Manado - Pambudi, Denny; Tumboimbela, Melke; Tangkudung, Gilbert (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
ABSTRACT Introduction: Stroke is one of the causes of mortality and long-term disability in the world. Triglyceride ratio-high-density lipoprotein is an objective parameter that has been validated as a prognostic tool for outcome 3 months after ischemic stroke. Aim: To determine the relationship between triglyceride- high-density lipoprotein with ischemic stroke outcome. Methods: This study was a retrospective observational cross-sectional study in acute ischemic stroke patients treated at Prof dr. R. D Kandou Manado hospital taken by consecutive sampling. The bivariate test was analyzed using a simple linear regression method. Results: 150 acute ischemic stroke patients were included in this study, with an average age of 60.00Ã‚Â±10.10 years, compromising 57.3% men, and average TG/HDL ratio of 3.51. Barthel's outcomes with mild dependence were 62%, while the good mRS outcomes were 52.67%. Linear regression test of the TG/HDL ratio on the Barthel scale, obtained the value of r=0.19 and the value of R square=0.038, with a value of p=0.018, and the regression line equation of the Barthel value=65.31+(-1.27) TG/HDL ratio. Whereas to the mRS scale, the value of r=0.18 and the value of R square=0.032, with a value of p=0.028, and the regression line equation of the mRS value=3.058+0.60 TG/HDL ratio. Discussion: : TG/HDL ratio has a negative relationship on the Barthel scale and a positive relationship on the mRS scale, with a weak correlation value. TG/HDL ratio is considered as an independent parameter that predict ischemic stroke outcome. Keywords: Triglycerides, high-density lipoprotein , Ischemic Stroke, Outcome